Water In Food and Its Chemical Description - Sultonova Husnidakhan Hasanjon kizi (Genius Journals, 2024)
The water content in food products strongly affects their nutritional value, taste, and shelf life. The more water is contained in food, the less caloric they are, perishable and stored less. Therefore, in the established regulatory and technical documents for food products, the humidity norm will be prescribed.
Keywords: minerals; microelements; macronutrients